Actual management costs of patients with non-valvular atrial fibrillation treated with percutaneous left atrial appendage closure or oral anticoagulation. (14th October 2021) - D'Ancona, G; Arslan, F; Safak, E; Ince, H
Abstract: Background: Left atrial appendage closure (LAAC) is a safe and efficacious alternative to oral anticoagulation (OAC) therapy in patients with non-valvular atrial fibrillation (AF) who are at high risk for both stroke and bleeding. Data on cost-effectiveness of LAAO are limited and existing studies on the topic are based on simulation model approaches rather than on real-world costs. Purpose: To compare actual management costs in patients with non-valvular AF treated with LAAC or OAC only. Methods: Percutaneous LAAC was performed only in patients with at least one cerebral thromboembolic event, one major bleeding episode while under OAC, and with absolute contraindication to prolonged OAC. AF patients undergoing percutaneous LAAC were matched with AF patients treated with OAC only. Matching variables were gender, age, and Diagnosis Related Groups (DRG) clinical complexity level. Costs for cardiovascular outpatient clinic visits and hospitalizations were derived from the actual medical claims and reimbursement records. Data were prospectively collected and retrospectively analyzed. Results: Between 1/2012 and 12/2016, 8478 patients with non-Valvular AF were referred to our institution: 7801 (92%) were managed with OAC only and 677 (8%) with LAAC. A total of 559 patients (279 per group) were matched. Mean age was 74.9±7.5 years, 244 were female (43.7%), and mean DRG clinical complexity level was 1.8±1.1. Median annualized management cost before LAAC was €3110 (IQR €1281–8127). Median hospitalization cost for LAAC was €9601 (IQR: €9393–10007). After a mean follow-up of 4.5±1.4 years, median annualized management cost was €1297 (€607–2735) in patients with sole OAC and €1013 (IQR €0–4770) in patients after LAAC (p=0.003). Undergoing LAAC was the strongest independent determinant to reduce follow-up management costs (linear regression: beta = −0.335; CI: −1.09 to −0.682; p<0.0001). Estimated 3-year survival was similar in the LAAC (92%) and OAC patients (90%) (p=0.7). Conclusion: LAAC significantly reduces management costs of patients with non-valvular AF. In patients referred for percutaneous LAAC, the drastic reduction in management costs following LAAC justifies the procedural costs. In spite of their complex comorbid profile, LAAC patients show a follow-up survival rate similar to those of patients solely treated with OAC. Management costs of patients solely on OAC are significantly higher than management costs of patients after LAAC. Future studies are necessary to investigate the potential net economic and clinical benefit of LAAC in patients that are treated with OAC only. Funding Acknowledgement: Type of funding sources: None.